Covariation in patterns of turbulence‐driven hyporheic flow and denitrification enhances reach‐scale nitrogen removal. Issue 8 (17th August 2017) - Li, Angang; Aubeneau, Antoine F.; Bolster, Diogo; Tank, Jennifer L.; Packman, Aaron I.
Abstract: Coinjections of conservative tracers and nutrients are commonly used to assess travel time distributions and nutrient removal in streams. However, in‐stream tracer data often lack information on long‐term hyporheic storage, and removal rate coefficients are often assumed to be uniform despite plentiful evidence that microbially mediated transformations, such as denitrification, exhibit strong spatial variability in the hyporheic zone. We used process‐based particle‐tracking simulations to explore the coupled effects of spatial patterns in hyporheic flow and denitrification on reach‐scale nitrogen removal. We simulated whole‐stream nitrogen dynamics with exponential, layered, and uniform profiles of hyporheic denitrification. We also simulated nitrogen dynamics in Little Rabbit Creek, an agricultural headwater stream in the Kalamazoo River Basin (Michigan, USA) where vertical profiles of hyporheic denitrification were measured in situ. Covariation between pore water velocity and mixing causes rapid exchange in the near‐surface bioactive region and substantially prolonged exchange in the deeper hyporheic. Patterns of hyporheic denitrification covary with patterns of hyporheic flow. This covariation directly controls tailing of in‐stream breakthrough curves and hence reach‐scale nutrient removal. Enhanced denitrification near the sediment‐water interface strongly tempers breakthrough curve tails at time scales associated with flushing of the near‐surface region, while more spatially uniform denitrification causes weaker tempering over a wider range of hyporheic exchange time scales. At the reach scale, overall nitrogen removal increases with heterogeneity of hyporheic denitrification, indicating that covariation between flow and denitrification—particularly the rapid flushing of highly bioactive regions near the sediment‐water interface—controls whole‐stream transformation rates. Key Points: We develop a stochastic particle‐tracking model to simulate flow‐denitrification interactions across the stream‐hyporheic continuum Nutrient uptake from the stream is controlled primarily by flushing of highly bioactive regions near the sediment‐water interface Covariation in patterns of hyporheic flow and denitrification cause reach‐scale nitrogen removal to increase with subsurface heterogeneity